Photophysical Analysis of Aggregation-Induced Emission (AIE) Luminogens Based on Triphenylamine and Thiophene: Insights into Emission Behavior in Solution and PMMA Films (2024)
Aggregation-Induced Emission (AIE) luminogens have garnered significant interest due to their distinctive applications in different applications. Among the diverse molecular architectures, those based on triphenylamine and thiophene hold prominence. However, a comprehensive understanding of the deactivation mechanism both in solution and films remains lacking. In this study, we synthesized and characterized spectroscopically two AIE luminogens: 5-(4-(bis(4-methoxyphenyl)amino)phenyl)thiophene-2-carbaldehyde (TTY) and 5′-(4-(bis(4-methoxyphenyl)amino)phenyl)-[2,2′-bithiophene]-5-carbaldehyde (TTO). Photophysical and theoretical analyses were conducted in both solution and PMMA films to understand the deactivation mechanism of TTY and TTO. In diluted solutions, the emission behavior of TTY and TTO is influenced by the solvent, and the deactivation of the excited state can occur via locally excited (LE) or twisted intramolecular charge transfer (TICT) state. In PMMA films, rotational and translational movements are constrained, necessitating emission solely from the LE state. Nevertheless, in the PMMA film, excimers-like structures form, resulting in the emergence of a longer wavelength band and a reduction in emission intensity. The zenith of emission intensity occurs when molecules are dispersed at higher concentrations within PMMA, effectively diminishing the likelihood of excimer-like formations. Luminescent Solar Concentrators (LSC) were fabricated to validate these findings, and the optical efficiency was studied at varying concentrations of luminogen and PMMA.